A Review of the Application of Virtual Reality Technology in the Diagnosis and Treatment of Cognitive Impairment - Liu, Yao; Tan, Wenjun; Chen, Chao; Liu, Chunyan; Yang, Jinzhu; Zhang, Yanchun (Frontiers in Aging Neuroscience, 2019)
At present, with the development of the aging society and the increase of the number of the elderly, in order to ensure the ability and enthusiasm of the elderly to live independently, it is necessary to ensure that they can understand the world in a normal way. However, more and more elderly people have cognitive impairment, and virtual reality technology can produce more effective results in cognitive diagnosis and treatment than the introduction of traditional methods. This review describes some studies on cognitive diagnosis and training for the elderly, and puts forward some suggestions for the current studies, hoping that VR technology can be better applied to cognitive diagnosis and training.